Estrutura populacional de Callinectes ornatus Ordway (Crustacea, Portunidae) no Balneário Shangri-Lá, Pontal do Paraná, Paraná, Brasil - Baptista, Cassiana; Pinheiro, Marcelo A. Amaro [UNESP]; Blankensteyn, Arno; Borzone, Carlos A. (Sociedade Brasileira de Zoologia, 2003)
Swimming crabs are commonly found in the otter-trawl shrimp fishery by-catch, which operate intensively in the Coastal Plain of Leste Beach, where is located Shangri-lá Beach (25°37'30S and 48°25'08W), Paraná State. This work aimed to study the population structure of Callinectes ornatus Ordway, 1863, the most abundant swimming crab in this beach. Between March 2000 and April 2001, fortnightly visits were accomplished in Shangri-lá at the fish market, where all swimming crabs of one otter-trawl were collected. The following data from each individual of C. ornatus were obtained: sex, carapace width (excluding lateral spines), weight, and the gonadal maturation stage, based on its color and size. Juveniles and mature males were dominant, mean sexual proportion was 2.2:1 (males:females). Two recruitment periods were detected, but few ovigerous females were obtained. Size at sexual maturation was estimated at 55mm for males, and 48 mm for females. Both sexes presented positives allometric growths. The results indicate that an important portion of C. ornatus population is captured in the otter-trawl shrimp fishery in Shangri-lá Beach (Paraná). Such information is important for futures plans of by-catch management in that area.
Population structure of C. ornatus Ordway (Crustacea, Portunidae) in Shangri-lá Beach, Pontal do Paraná, Paraná, Brazil
Keywords: By-catch; maturity; population biology; sex ratio; swimming crab